Antifungal Activity of Thai Cajuput Oil and Its Effect on Efflux-Pump Gene Expression in Fluconazole-Resistant Candida albicans Clinical Isolates - Pitchayaphong Keereedach; Karnjana Hrimpeng; Khaemaporn Boonbumrung (International Journal of Microbiology)
Candidiasis caused by the fluconazole-resistant opportunistic pathogen Candida albicans is an intractable clinical problem that threatens immunocompromised or normal individuals. The most common mechanism of fluconazole resistance in C. albicans is the failure of cells to accumulate the drug due to increased expression of the efflux proteins encoded by the CDR1, CDR2, and MDR1 genes. Because the number of current antifungal drugs is limited, it is necessary to develop new therapeutic strategies. This study aimed to evaluate the antifungal activity of Thai Cajuput oil, its synergism with fluconazole, and its effect on efflux-pump gene expression in fluconazole-resistant C. albicans clinical isolates. Thus, we first detected the efflux-pump genes in fourteen resistant strains by PCR. The frequencies of the CDR1, CDR2, and MDR1 genes were 68.75%, 62.5%, and 87.5%, respectively, and these efflux-pump genes were distributed in three distinct patterns. Subsequently, the antifungal activity of Thai Cajuput oil was assessed by broth macrodilution and its synergism with fluconazole was evaluated by the checkerboard assay. The changes in the expression levels of CDR1, CDR2, and MDR1 after treatment with Thai Cajuput oil were analyzed by qRT-PCR. The MICs and MFCs of Thai Cajuput oil ranged from 0.31 to 1.25 μl/ml and 0.63 to 1.25 μl/ml, respectively, and its activity was defined as fungicidal activity. The MICs of the combination of Thai Cajuput oil and fluconazole were much lower than the MICs of the individual drugs. Interestingly, sub-MICs of Thai Cajuput oil significantly reduced the MDR1 expression level in resistant strains P<0.05. Our study suggests that Thai Cajuput oil can be used to create new potential combination therapies to combat the antifungal resistance of C. albicans.